2007
DOI: 10.1038/sj.hdy.6801073
|View full text |Cite
|
Sign up to set email alerts
|

The tragedy of the commons in microbial populations: insights from theoretical, comparative and experimental studies

Abstract: First principles of thermodynamics imply that metabolic pathways are faced with a trade-off between the rate and yield of ATP production. Simple evolutionary models argue that this trade-off generates a fundamental social conflict in microbial populations: average fitness in a population is highest if all individuals exploit common resources efficiently, but individual reproductive rate is maximized by consuming common resources at the highest possible rate, a scenario known as the tragedy of the commons. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 27 publications
1
117
0
Order By: Relevance
“…Warmer conditions enhance metabolic rates (BROWN et al, 2004), which also leads to higher energetic loss (MACLEAN, 2008;PFEIFFER et al, 2001). Therefore, water temperatures are often directly correlated to bacterial production and respiration (JIMENEZ-MERCADO et al, 2007;KIRCHMAN et al, 2005;POMEROY et al, 1995;RAYMOND;BAUER, 2000; SAMPOU; KEMP, 1994; SHIAH; DUCKLOW, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Warmer conditions enhance metabolic rates (BROWN et al, 2004), which also leads to higher energetic loss (MACLEAN, 2008;PFEIFFER et al, 2001). Therefore, water temperatures are often directly correlated to bacterial production and respiration (JIMENEZ-MERCADO et al, 2007;KIRCHMAN et al, 2005;POMEROY et al, 1995;RAYMOND;BAUER, 2000; SAMPOU; KEMP, 1994; SHIAH; DUCKLOW, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of thermodynamic (and partly experimental, see MacLean, 2008;Novak et al, 2006) arguments, a trade-off between yield and rate in ATP production was shown theoretically to lead to a "tragedy of the commons" (MacLean, 2008;Pfeiffer et al, 2001). The basic idea is that organisms have two options: either convert substrate into biomass efficiently, but slowly, or consume the substrate fast with concomitant fast growth, but inefficiently.…”
Section: Adaptations In Metabolic Network Behaviormentioning
confidence: 99%
“…Defector strains, which fail to pay the cost of cooperation but receive the benefits, may exhibit higher fitness and quickly dominate the population. A variety of mechanisms exist to circumvent this game-theoretical constraint and allow cooperative phenotypes to thrive (Brännströ m and Dieckmann 2005;Nowak 2006;MacLean 2008;Chuang et al 2010).…”
Section: Evolutionary Stabilitymentioning
confidence: 99%